A companion to ancient Near Eastern languages - Hasselbach, Rebecca (Hoboken Wiley Blackwell, 2020)
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- List of Tables -- Notes on Contributors -- Preface -- PART I WRITING SYSTEMS -- Chapter One The Decipherment of Ancient Near Eastern Languages -- Introduction -- Types of Decipherment -- Processes in Decipherment -- Accounts of Decipherment -- Notes -- References -- Chapter Two The Emergence of Cuneiform Writing -- Introduction -- The Context of Proto-Cuneiform, Its Precursors and Origins -- The Archaic Text Corpus and Cuneiform Script Characteristics -- Structural Organization and Sign Types -- Relationship with Sumerian -- Notes -- References -- Chapter Three The Development of Egyptian Writing in the Fourth and Early Third Millennium bce -- Introduction -- Working Definition of Script and its Relation to Other Graphic Communication Systems -- The Rebus Principle and the Phoneticization of Pictures -- Radical Phoneticization in Graphophonic Writing: Mono-Consonantal Signs -- Developmental Stages of the Early Script in the Nile Valley - a Historical Sketch of the First 500 Years -- The Egyptian Script and its Relation to the Visual Mode of Gestural Communication -- The Question of Language Versus Languages: Multilingualism in the Nile Valley in the Fourth Millennium bce and the Question of the Correlation Between Language - Culture - State(s): -- Standardization and Formalization -- Abandoned Innovations, Removal of Cultural Residue, Breaks in Traditions -- Coda -- Notes -- References -- Chapter Four The Emergence of Alphabetic Scripts -- The Earliest Evidence for the Alphabet and its Iconic Models in Egyptian -- The Broader Usage of Early Alphabetic in the Second Millennium -- The Inventors of the Alphabet: Elite Semites Familiar with the Egyptian Writing System -- The Transition from Early Alphabetic to Phoenician: The Center and the Periphery.
Description based on publisher supplied metadata and other sources
Keywords: Extinct languages-Middle East; Electronic books; Aufsatzsammlung